The Effectiveness Of Monosodium Glutamate And Types Ofplanting Media On The Growth Of Orchid Plant (Dendrobium sp) In Acclimatization Phase - Suharman Suharman; Nurhapisah Nurhapisah (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2021)
The need for orchids in Indonesia are still very large, including the Dendrobium